Sampling in modern pharmaceutical analysis - T. N. Bokovikova; E. P. Gernikova; E. I. Sakanyan; N. D. Bunyatyan; L. I. Shishova; L. A. Stronova; S. A. Manaeva (Регуляторные исследования и экспертиза лекарственных средств, 2018)
Sampling procedure is an integral part of the drug quality control system. Objective science-based sampling is an important operation when only a small amount of a material is taken and it is representative for the analysis of the whole product batch. Reasoned conclusions about drug quality can only be based on the results of tests conducted on representative samples, taken in accordance with certain rules and regulations. For the purpose of harmonization with foreign normative documents, systematization and updating of the requirements for sampling, specifying their conditions, general pharmacopoeia monograph «Sampling» has been developed. It regulates general rules and special aspects of drug sampling procedures for the purpose of drug quality control. The general pharmacopoeia monograph «Sampling» consolidates and classifies the materials of legislative and regulatory documents of the Russian Federation, the WHO, the EU and international pharmacopoeia monographs.